An intelligent hybrid-fabric wristband system enabled by thermal encapsulation for ergonomic human-machine interaction - Aobo Cheng; Xin Li; Ding Li; Zhikang Chen; Tianrui Cui; Lu-Qi Tao; Jinming Jian; HuiJun Xiao; Wancheng Shao; Zeyi Tang; Xinyue Li; Zirui Dong; et al. (Nature Communications)
Abstract Human-machine interaction has emerged as a revolutionary and transformative technology, bridging the gap between human and machine. Gesture recognition, capitalizing on the inherent dexterity of human hands, plays a crucial role in human-machine interaction. However, existing systems often struggle to meet user expectations in terms of comfort, wearability, and seamless daily integration. Here, we propose a handwriting recognition technology utilizing an intelligent hybrid-fabric wristband system. This system integrates spun-film sensors into textiles to form the smart fabric, enabling intelligent functionalities. A thermal encapsulation process is proposed to bond multiple spun-films without additional materials, ensuring the lightweight, breathability, and stretchability of the spun-film sensors. Furthermore, recognition algorithms facilitate precise accurate handwriting recognition of letters, with an accuracy of 96.63%. This system represents a significant step forward in the development of ergonomic and user-friendly wearable devices for enhanced human-machine interaction, particularly in the virtual world.